The Result of Elections to the Śląskie Voivodeship Assembly in 2018 in Reality of the Territorial Heteronomy - Myśliwiec, Małgorzata (Political Preferences, 2019)
The main aim of the paper is the theoretical analysis of the concept of the territorial heteronomy. Conclusions concerning the idea of territorial autonomy, regionalism or federalism easily can be found in the scientific literature. But they are useless to investigate and explain many political processes and political preferences in states of the Central and Eastern Europe. It is because states of this part of the continent did not have a chance to create and develop their own models of classic administration institutions in the nineteenth century, inter alia the local and regional government. Their only experience in this area is limited to the interwar period between 1918 and 1939. They have gained a new chance for a democratic division of public tasks after the collapse of the communist system in the very end of the twentieth century. But in that period they have focused more on the horizontal division of powers than on the vertical one. For that reason up till today political phenomena in the political centre have more importance than the regional policy impact attempts. The inspiration for such a research were electoral results obtained by two regional parties at elections to the Śląskie Voivodeship Assembly in 2018.